Carbon Footprint for energy efficiency in public buildings - Karina Fraczek; Jerzy Śleszyński (Economic and Environmental Studies (E&ES), 2015)
The paper presents an empirical analysis of Carbon Footprint indicator applied to the public building of the Faculty of Chemistry at the University of Warsaw. Analysis takes into account direct and indirect CO2 emissions related to the functioning of the Faculty. Analysis concentrates on the year 2013 but also allows for some comparison with two earlier years and with two other public buildings in Warsaw. The final outcome of this study, with a help of thermo visual examinations, proposes a list of undertakings which are necessary to improve the efficient use of energy in the Faculty.
Keywords: Q54; Q52; Q57; 330; Carbon Footprint; energy efficiency; public building